2018
DOI: 10.3847/1538-4357/aab3c6
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Broad-line Region Geometry and Dynamics in Arp 151 Over Seven Years

Abstract: The Seyfert 1 galaxy Arp 151 was monitored as part of three reverberation mapping campaigns spanning 2008-2015. We present modeling of these velocity-resolved reverberation mapping data sets using a geometric and dynamical model for the broad-line region (BLR). By modeling each of the three data sets independently, we infer the evolution of the BLR structure in Arp 151 over a total of 7 yr and constrain the systematic uncertainties in nonvarying parameters such as the black hole mass. We find that the BLR geom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 76 publications
7
69
0
Order By: Relevance
“…It is consistent with the results by the BLRs dynamical model to fit simultaneously the AGNs continuum/Hβ light curves and Hβ line profiles (e.g. Li et al 2018;Pancoast et al 2018;Williams et al 2018).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is consistent with the results by the BLRs dynamical model to fit simultaneously the AGNs continuum/Hβ light curves and Hβ line profiles (e.g. Li et al 2018;Pancoast et al 2018;Williams et al 2018).…”
Section: Introductionsupporting
confidence: 91%
“…MBH from the BLR dynamical method, where the virial factor fBLR is directly constrained from velocity-resolved reverberation mapping. (e.g Li et al 2018;Pancoast et al 2018;Williams et al 2018…”
mentioning
confidence: 99%
“…In this work we model the structure of the BLR of a sample of low redshift AGN using the model presented by R19. This model is a modified version of the BLR model of Pancoast et al (2018), first presented by Pancoast et al (2011). Our model uses single-epoch spectra (as opposed to monitoring data) to constrain the geometry and dynamics parameters of the BLR.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In previous versions of the model, the generated continuum light curve was constrained based on the observed continuum light curve as determined from monitoring campaigns (e.g. Pancoast et al 2014b, Grier et al 2017, Pancoast et al 2018, Williams et al 2018. In our version of the model, where we use only a single spectrum instead of monitoring data, we do not have an observed light curve to analyse (R19).…”
Section: A Single-epoch Broad Line Region Modelmentioning
confidence: 99%
“…The transfer function describes the emission line response to the continuum variability and is related to the physical structure and kinematics of the BLR (Blandford & McKee 1982). The choice of the transfer function width is motivated by velocity-resolved lag observations (e.g., Grier et al 2013;Skielboe et al 2015;Pancoast et al 2018), but we have tested different transfer function widths and found that the results are insensitive to this detail (e.g., Shen et al 2015a).…”
Section: Simulationsmentioning
confidence: 99%